(Co)homology of triassociative algebras - Donald Yau (International Journal of Mathematics and Mathematical Sciences)
We study homology and cohomology of triassociative algebras with nontrivial coefficients. The cohomology theory is applied to study algebraic deformations of triassociative algebras.